Palmitoylated mNeonGreen Protein as a Tool for Visualization and Uptake Studies of Extracellular Vesicles - Wąchalska, Magda (Membranes (Basel), 2020)
Extracellular vesicles (EVs) are membranous nanoparticles released by cells as vital mediators of intercellular communication. As such, EVs have become an attractive target for pathogens and cancer cells, which can take control over their cargo composition, as well as their trafficking, shaping the pathogenesis. Despite almost four decades of research on EVs, the number of specific and efficient EV labeling methods is limited, and there is still no universal method for the visualization of their transport in living cells. Lipophilic dyes that non-specifically intercalate into the EVs membranes may diffuse to other membranes, leading to the misinterpretation of the results. Here, we propose a palmitoylated fluorescent mNeonGreen (palmNG) protein as an alternative to chemical dyes for EVs visualization. The Branchiostoma lanceolatum-derived mNeonGreen is a brighter, more stable, and less sensitive to laser-induced bleaching alternative to green fluorescent protein (GFP), which makes it a more potent tag in a variety of fluorescence-based techniques. A palmNG-expressing stable human melanoma cell line was generated using retrovirus gene transfer and cell sorting. This protein partially localizes to cellular membranes, and can be detected inside size-exclusion (SEC)-purified EVs. With the use of flow cytometry and fluorescent confocal microscopy, we performed qualitative and quantitative analyses of palmNG-EVs uptake in recipient human hepatoma cells, in comparison to PKH67-labeled vesicles. Our findings confirm that membrane-embedded mNeonGreen can be successfully applied as a tool in EVs transfer and uptake studies.